Raineyella fluvialis sp. nov., an actinobacterium isolated from freshwater sediment. Issue 7 (26th July 2020) - Kim, Yeon Bee; Kim, Joon Yong; Song, Hye Seon; Lee, Changsu; Kim, Juseok; Whon, Tae Woong; Lee, Se Hee; Rhee, Jin-Kyu; Roh, Seong Woon
Abstract : A novel, facultatively anaerobic actinobacterium, designated strain CBA3103 T, was isolated from sediment of the Geum River in South Korea. Phylogenetic analysis indicated that strain CBA3103 T is most closely related to Raineyella antarctica LZ-22 T (98.47 % 16S rRNA gene sequence similarity). The genome of strain CBA3103 T was 3 649 865 bp with a DNA G+C content of 69.6 mol%. The average nucleotide identity value between strain CBA3103 T and R. antarctica LZ-22 T was 79.22 %. Cells of strain CBA3103 T were Gram-positive, rod-shaped, 0.6–0.9 µm wide and 1.4–2.4 µm long. Growth occurred at 15–40 °C (optimum, 35 °C), at pH 6.0–7.0 (optimum, pH 7.0) and with 0–2 % NaCl (w/v) (optimum, 0–1 %, w/v). The major cellular fatty acids in strain CBA3103 T were anteiso-C15 : 0, anteiso-C15 : 1 A and iso-C14 : 0 . The major respiratory quinone was menaquinone-9(H4 ). The polar lipids of strain CBA3103 T were diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine, five unidentified glycolipids and three unidentified phospholipids. Based on the genotypic, phenotypic and chemotaxonomic analyses, strain CBA3103 T represents a novel species of the genus Raineyella, for which the name Raineyella fluvialis sp. nov. (type strain CBA3103 T =KACC 21446 T =DSM 110288 T ) is proposed.